ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SISWA KELAS VIII PADA MATERI BANGUN DATAR SEGITIGA DAN SEGI EMPAT - Sigit Mulqiyono; Debby Yuniar; Ika Wahyu Anita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This preliminary study aims to analyze the mastery of mathematical communication skills of class VIII students in junior high school in Bandung regency of triangular and rectangular flat building material. In this preliminary study, the research method used is a qualitative descriptive method with 5 students of class VIII as a sample and research instruments used are 5 items about the instrument of mathematical communication ability. Based on the observations made on 5 students it is found that mastery of mathematical communication skills owned by grade VIII students in one junior high school in Bandung Regency is still relatively low.